Choroid plexus genes for CSF production and brain homeostasis are altered in Alzheimer’s disease - Kant, Shawn; Stopa, Edward G.; Johanson, Conrad E.; Baird, Andrew; Silverberg, Gerald D. (Fluids and barriers of the CNS, 2018)
Background The roles of the choroid plexus (CP) and cerebrospinal fluid (CSF) production have drawn increasing attention in Alzheimer’s disease (AD) research. Specifically, studies document markedly decreased CSF production and turnover in moderate-to-severe AD. Moreover, reduced CP function and CSF turnover lead to impaired clearance of toxic metabolites, likely promote neuroinflammation, and may facilitate neuronal death during AD progression. We analyzed CP gene expression in AD compared with control subjects, specifically considering those genes involved with CSF production and CP structural integrity. Methods The Brown-Merck Gene Expression Omnibus (GEO) database (CP transcripts) was mined to examine changes in gene expression in AD compared to controls with a focus on assorted genes thought to play a role in CSF production. Specifically, genes coding for ion transporters in CP epithelium (CPE) and associated enzymes like Na–K-ATPase and carbonic anhydrase, aquaporins, mitochondrial transporters/enzymes, blood–cerebrospinal fluid barrier (BCSFB) stability proteins, and pro-inflammatory mediators were selected for investigation. Data were analyzed using t test p-value and fold-change analysis conducted by the GEO2R feature of the GEO database. Results Significant expression changes for several genes were observed in AD CP. These included disruptions to ion transporters (e.g., the solute carrier gene SLC4A5, p = 0.004) and associated enzyme expressions (e.g., carbonic anhydrase CA4, p = 0.0001), along with decreased expression of genes involved in BCSFB integrity (e.g., claudin CLDN5, p = 0.039) and mitochondrial ATP synthesis (e.g., adenosine triphosphate ATP5L, p = 0.0004). Together all changes point to disrupted solute transport at the blood–CSF interface in AD. Increased expression of pro-inflammatory (e.g., interleukin IL1RL1, p = 0.00001) and potential neurodegenerative genes (e.g., amyloid precursor APBA3, p = 0.002) also implicate disturbed CP function. Conclusions Because the altered expression of numerous transcripts in AD-CP help explain decreased CSF production in AD, these findings represent a first step towards identifying novel therapeutic targets in AD.